Preventing Subsequent Teenage Pregnancy: A Multisite Analysis of Goal Orientation and Social Supports. Issue 4 (17th October 2020) - Kan, Marni L; Ramirez, Derek D
Abstract: Subsequent teenage births may present various challenges for teenage parents and their children. Evaluation of efforts to prevent subsequent teenage pregnancy and increase use of long-acting reversible contraception (LARC) have lacked investigation of the mechanisms—particularly, goal orientation and social supports—through which these efforts may be effective. Data were from a multisite evaluation of the Title XX Adolescent Family Life program, which involved 12 demonstration projects comparing enhanced and core services to pregnant and parenting teenagers. Data from 857 female teenagers at baseline and follow-up were used in analyses. Multivariate regression models examined associations between independent variables (study condition and effective project characteristics) and mediators (orientation toward goals and social supports) and between mediators and outcomes (subsequent pregnancy and use of LARC). Structural equation models tested mediation pathways. The program and selected project characteristics significantly predicted decreased coresidence with parents, and support from the child's father was associated with higher LARC use. However, neither orientation toward goals nor social supports mediated program effects on LARC use or subsequent pregnancy. Programs to prevent subsequent teenage pregnancy may encourage teenagers' independence from families of origin and should consider promoting supportive relationships with the child's father.